3D-ordered porous nitrogen and sulfur Co-Doped carbon supported PdCuW nanoparticles as efficient catalytic cathode materials for Li-O2 batteries. (10th May 2018) - Lin, Sen; Li, Yongliang; Luo, Shan; Ren, Xiangzhong; Deng, Libo; Mi, Hongwei; Zhang, Peixin; Sun, Lingna; Gao, Yuan
Abstract: 3D-ordered porous nitrogen and sulfur co-doped carbon (NS/C) is synthesized from the functionalized fluidic acrylonitrile telomer (ANT) as C, N and S source. The dispersed PdCuW nanoparticles with an average size of 5.25 nm are supported on the walls of the NS/C by a glycol reduction method. Compared with 20%Pd black (Pd/C), NS/C and 20%Pd-NS/C, it is found that PdCuW-NS/C composite with 11.4 wt% Pd exhibits superior catalytic activity for oxygen reduction reaction (ORR) in alkaline solution. Moreover, PdCuW-NS/C possesses higher capacities, lower overpotentials and better cyclic stability as cathode materials for Li-O2 batteries; the cyclic retention of more than 70 cycles are achieved at 300 mA g −1 with the restricted capacity at 500 mAh g −1 .